Radiation induced skin reactions during and following radiotherapy: A systematic review of interventions. Issue 1 (February 2022) - Burke, G.; Faithfull, S.; Probst, H.
Abstract: Introduction: Radiation induced skin reactions (RISR) are a common adverse effect of radiotherapy that can impact on patient quality of life. The aim of this systematic review was to identify new research evidence on interventions for RISR to guide health practitioners on best practice skin care for people receiving radiotherapy. Methods: A narrative systematic review was adopted including published research since 2014. The MESH search terms used in the 2014 College of Radiographers skin care systematic review were supplemented with terms identified through a pearl growing search technique. Results: Thirty-three studies were identified and reviewed, 13(39.4%) were assessed as having a high risk of bias 6(18.2%) moderate risk of bias, and 13(39.4%) low risk of bias; one pilot study was not assessed. Twenty-one of the studies were randomised controlled trials, 2 feasibility studies, 9 non-randomised trials, and 1 a pilot study. Conclusion: Evidence from well conducted studies identified prophylactic use of steroid cream for patients, at high risk of RISR, as being the most efficacious in reducing acute skin reactions. Further research is needed on photo biomodulation therapy, studied within standard dose fractionation schedules, before it is recommended for use in practice. There is insufficient evidence to support the use of barrier films or any topical emollients currently in practice to reduce RISRs. Despite the number of new studies in this area there is limited good comparative research of RISR that accounts for predictive risk and new radiotherapy techniques. Implications for practice: Practitioners are encouraged to risk assess patients prior to radiotherapy to guide interventions and record and monitor patient skin toxicity regularly during treatment, comparing toxicity changes with scores recorded at baseline and support patient self-monitoring of skin reactions.